Determination of variability due to biological and technical variation in urinary extracellular vesicles as a crucial step in biomarker discovery studies. Issue 1 (13th October 2019) - Oeyen, Eline; Willems, Hanny; 'T Kindt, Ruben; Sandra, Koen; Boonen, Kurt; Hoekx, Lucien; De Wachter, Stefan; Ameye, Filip; Mertens, Inge
ABSTRACT: Urinary extracellular vesicles (EVs) are an attractive source of biomarkers for urological diseases. A crucial step in biomarker discovery studies is the determination of the variation parameters to perform a sample size calculation. In this way, a biomarker discovery study with sufficient statistical power can be performed to obtain biologically significant biomarkers. Here, a variation study was performed on both the protein and lipid content of urinary EVs of healthy individuals, aged between 52 and 69 years. Ultrafiltration (UF) in combination with size exclusion chromatography (SEC) was used to isolate the EVs from urine. Different experimental variation set‐ups were used in this variation study. The calculated standard deviations (SDs) of the 90% least variable peptides and lipids did not exceed 2 and 1.2, respectively. These parameters can be used in a sample size calculation for a well‐designed biomarker discovery study at the cargo of EVs.